Lazar on "Moral Sunk Costs" and the "Discount View". (17th March 2022) - Steinhoff, Uwe
Abstract: There is a question as to how already "sunk" costs enter into proportionality considerations. Lazar proposes the "Discount View, " in which the reasons to secure the goal progressively (with sunk costs) diminish in weight but not below a certain threshold. I argue that even if this happened, this would not solve the problem that motivates Lazar to reject the "Prospective View." Moreover, the mechanism Lazar proposes to make reasons behave in this way does not exist: There are no rights‐based reasons for pursuing the goal present in his paradigmatic example, only well‐being‐based reasons. This is implied by Lazar's own description of the case as one of rights‐infringement, which makes his position incoherent. Finally, the four arguments Lazar offers for these reasons' progressively diminishing in force are inconclusive anyway.